2014
DOI: 10.1152/jn.00084.2014
|View full text |Cite
|
Sign up to set email alerts
|

Kv7 channels regulate pairwise spiking covariability in health and disease

Abstract: Ocker GK, Doiron B. Kv7 channels regulate pairwise spiking covariability in health and disease. J Neurophysiol 112: 340 -352, 2014. First published April 30, 2014 doi:10.1152/jn.00084.2014.-Low-threshold M currents are mediated by the Kv7 family of potassium channels. Kv7 channels are important regulators of spiking activity, having a direct influence on the firing rate, spike time variability, and filter properties of neurons. How Kv7 channels affect the joint spiking activity of populations of neurons is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 78 publications
1
24
0
Order By: Relevance
“…Here, we present the results of dynamic-clamp experiments carried out in pyramidal cells and in fast-spiking (FS) and non-fast-spiking (NON-FS) interneurons from slices of rat cortical tissue. We found that, for low input correlation and across all cell types, the experimentally measured values of output covariance and their dependency on firing rate are in quantitative agreement with the values computed using linear response theory (Litwin-Kumar et al, 2011, Ocker andDoiron, 2014). Interestingly however, FS interneurons displayed significantly larger values of output covariance, making this cell type particularly suited for transmitting correlations to its postsynaptic targets.…”
Section: Introductionsupporting
confidence: 84%
“…Here, we present the results of dynamic-clamp experiments carried out in pyramidal cells and in fast-spiking (FS) and non-fast-spiking (NON-FS) interneurons from slices of rat cortical tissue. We found that, for low input correlation and across all cell types, the experimentally measured values of output covariance and their dependency on firing rate are in quantitative agreement with the values computed using linear response theory (Litwin-Kumar et al, 2011, Ocker andDoiron, 2014). Interestingly however, FS interneurons displayed significantly larger values of output covariance, making this cell type particularly suited for transmitting correlations to its postsynaptic targets.…”
Section: Introductionsupporting
confidence: 84%
“…Subthreshold cellular dynamics, such as spike frequency adaptation 101 or fast membrane tracking of slow synaptic inputs 92 also shape L and hence the transfer of correlation. Increased cellular heterogeneity between the postsynaptic neuron pair typically reduces ρ 38,102 , particularly when measured over short timescales 38,103,104 .…”
Section: Three Mechanisms Of Correlation Modulationmentioning
confidence: 99%
“…One way to distinguish the mechanisms underlying correlation modulation is to consider spiking correlations ρ as a function of the time window ( T ) over which they are computed, because different mechanism modulate correlations on different timescales 89,78,101 . In general, ρ increases with the time window 106 , as in the case of the feedforward model with non-plastic synapses (Fig.…”
Section: Three Mechanisms Of Correlation Modulationmentioning
confidence: 99%
“…90 M-current further contributes to subthreshold theta frequency oscillations and regulates coherent spiking of neuron populations. 91,92 The important role of M-current in keeping the balance between neuronal excitation and inhibition is emphasized by KCNQ2 and KCNQ3 mutations, which lead to an infantile epilepsy syndrome (benign familial neonatal convulsions, BFNC). 93 Studies with conditional KCNQ2 or KCNQ3 knockout mice indicated that KCNQ2, rather than KCNQ3, is the important player in the regulation of neuronal excitability.…”
Section: Kcnq Structure and Regulation By B-subunitsmentioning
confidence: 99%